Unsteadiness and Modal Analysis of Ridge Ice-Induced Separation in Post-Stall Conditions via IDDES - TAN Xue, ZHANG Chen, XU Wenhao, WANG Fuxin, WEN Minhua (Editorial Office of Journal of Shanghai Jiao Tong University, 2021)
High-resolution simulation of shear layer oscillation induced by ridge ice in post-stall condition is conducted via the improved delayed detached-eddy simulation (IDDES) method. The flow-field evolution characteristics of large scale separation in high Reynolds number condition are described. It is shown that the ridge ice and trailing edge of the lower surface induce the development of shear flow at the same time. The wall is not reattached by the shear layer induced by ridge ice, and the “up-wash” flow from the lower surface is interacted with the shear layer, which lead to the formation of large-scale coherent structures. Combined with the spectral analysis, the pressure pulsation located in the shear layer is characterized by two typical frequencies, which are associated with Kelvin-Helmholtz instability and appear as the vortex pairing and shedding. Based on the proper orthogonal decomposition, the dominant mode of pressure pulsation between shear layers is extracted as large-scale coherent structures. The same peak value is shown in power density spectrum of dominant mode temporal coefficient and lift coefficient, which indicates that the large-scale coherent structure is connected with lift fluctuation.